Formation Energy of Alpha-Cluster Pre-formation Probability for Cluster-Formation Model (مجلة المنصور, 2023)
The pre-formation factor, pre-formation probability or the amount of alpha clustering was recently and well determined using the cluster-formation model (CFM) for alpha decay nuclei. Alpha-cluster formation energy was proposed and used in this model to calculate the factor that is important to calculate the alpha decay width. A new formula for this energy was derived and its validity is investigated. This formula was successful to describe alpha clustering and it can be included in the calculation of any future work.